Interior of St. Peter's Church, Barbados - (:unkn) unknown (My University, 2018)
Interior of St. Peter's Church, Barbados. The inside of The St. Peters, Barbados church is presented in this photo. Three persons are sitting to the front of the left pews. The history of St. Peter’s Parish Church is closely related with that of the town of Speightstown and the civil parish in which it is located. The present Church dates back to 1837 and is situated on Church and Orange Streets. This building is designed in a Georgian Style, but heavily influenced by Gothic architecture. Built with a Belfry at its western side, it carries a medieval tower with ramparts, suggesting an earlier more sinister usage of the building, as a means of military defense. Taken from: http://stpeter.anglican.bb (Anglican Diocese of Barbados)
Landscape; Black & white ,4 x 6 in.
Keywords: Church; Parish; Pews; Interior; St. Peter; Barbados; Speightstown